Ø§Ù„ÙƒÙ„Ø§Ù… Ø§Ù„Ø®Ø¨Ø±ÙŠ ÙÙŠ Ø³ÙˆØ±Ø© Ø§Ù„Ù†Ø³Ø§Ø¡ (Ø¯Ø±Ø§Ø³Ø© ØªØÙ„ÙŠÙ„ÙŠØ© Ø¨Ù„Ø§ØºÙŠØ©) - Muhimmatul Ulya (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2017)
The Quran is one of the miracles of the Prophet Muhammad. One kemu'jizatan Qur'an is in terms of its linguistic. The Qur'an has a style that is very beautiful and precise diction. One style of language in which the Koran is the word of the news (kalam khabar). Forms khabar kalam in the Qur'an is not only meaningful but has a distinctive purpose khabar. To determine the intent required carefulness in analyzing the context of the verses of the Koran. From this the researchers are keen to discuss the style of the language of the Koran, especially kalam khabar). As the focal point in this discussion is the problem: The approach used in the study of this literature is the analysis method balaghah, namely in terms of the science of al-Ma'ani. The results obtained by the author in this discussion are as many as 364 forms consisting of kalam khobar khobar kalam ibtidai 279, 73 and 12 tholabi kalam kalam khobar khobar Inkari. While the purpose of â€œkalam khobariâ€ many as 282 kinds.